GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 13644 species occurrences available in GBIF matching the query: TaxonKey: Gadus morhua Linnaeus, 1758 HasGeospatialIssue: false Geometry: POLYGON((-14.63 54.65,-14.63 70.39,40.47 70.39,40.47 54.65,-14.63 54.65)). The dataset includes 13644 records from 38 constituent datasets: 12 records from Marine species distributions in Irish coastal waters. 60 records from Marine Biological Association - Volunteer sightings data held by the DASSH Data Archive Centre. 3 records from Fishbase. 9364 records from SLU Aqua Institute of Coastal Research Database for Coastal Fish - KUL. 7 records from BioFokus. 105 records from Artdata. 48 records from Joint Nature Conservation Committee - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by JNCC. 466 records from Norwegian Biodiversity Information Centre - Other datasets. 1 records from iNaturalist Research-grade Observations. 2 records from KUBI Ichthyology Tissue Collection. 6 records from Diveboard - Scuba diving citizen science observations. 1 records from Porcupine Marine Natural History Society - Marine flora and fauna records from the North-east Atlantic. 2 records from naturgucker. 1 records from Marine Biological Association - Marine Life Survey Data (collected by volunteers) collated by MarLIN. 7 records from Benthos counted on dredged samples during Valdivia cruise VA44. 16 records from Benthos counted on dredged samples during Valdivia cruise VA53. 1 records from Natural History Museum (London) Collection Specimens. 2 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Dana00/5. 2 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Cirolana00/5. 4 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Tridens00/5. 8 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during two Michael Sars cruises in 2000. 572 records from Distribution of 15 major fish species in the North Sea between 1959 and 1979. 2257 records from HMAP-History pf Marine Animal Populations (CoML). 2 records from Taxonomic Information Sytem for the Belgian coastal area (EurOBIS). 2 records from A comparison of benthic biodiversity in the North Sea, English Channel and Celtic Seas (EurOBIS). 10 records from University Marine Biological Station Millport - 1999-2009 UMBSM Clyde Sea Fairlie Channel Beam Trawl Survey. 5 records from Sponges of Rathlin Island. 1 records from Vertebrate Zoology Division - Ichthyology, Yale Peabody Museum. 7 records from Collection Pisces SMF. 5 records from Geographically tagged INSDC sequences. 415 records from Norwegian Species Observation Service. 7 records from Marine Biological Association - Marine survey data (Professional) held by MarLIN.. 164 records from Marine Conservation Society - Seasearch Marine Surveys. 5 records from Centre for Environmental Data and Recording - Marine Data from Northern Ireland. 11 records from Scottish Natural Heritage - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by Scottish Natural Heritage. 3 records from Colección de referencia de otolitos, Instituto de Ciencias del Mar-CSIC. 53 records from Fish collection, Natural History Museum, University of Oslo. 7 records from Fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris).
Keywords: GBIF; biodiversity; species occurrences